Planning for environmental justice - reducing well-being inequalities through urban greening. Issue 112 (October 2020) - Liotta, Charlotte; Kervinio, Yann; Levrel, Harold; Tardieu, Léa
Highlights: Green spaces are unequally distributed within the Paris metropolitan area. Targeting areas poorly endowed with green space is likely to favour affluent populations. We propose a new methodology for just green infrastructure development. Abstract: Urban green spaces provide cultural ecosystem services, and urban policies typically aim to enhance these services by targeting new investments in deprived areas. The implementation of urban greening policies is one way to reduce inequalities in well-being, for example by targeting areas where increased access to green spaces will benefit citizens of low socioeconomic status. Most research has addressed the targeting of green infrastructure development by considering income and access to green spaces, while few studies have considered a multidimensional definition of well-being. The aims of this paper are to i) integrate inputs from the economic and political philosophy literature to propose a broader definition of well-being, including health, education, insecurity, and social relations; ii) develop a criterion to prioritise areas where urban greening would have the greatest impact on well-being inequalities; and iii) apply this criterion to the Paris metropolitan area (Ile-de-France region), a spatially heterogeneous region where areas deprived of access to green spaces are not systematically deprived in other dimensions. Our analysis shows that the city of Paris and the inner suburbs would be targeted when considering inequality in access to green spaces only. The results differ when inequalities in income or multidimensional well-being are taken into account, in which case the northern inner suburbs and some outer suburbs become a higher priority.